Statistical Methods for Survival Data Analysis. - Lee, Elisa T. (Wiley series in probability and statistics, 2013)
Praise for the iThird Edition/i/ ". . . an easy-to read introduction to survival analysis which covers the major concepts and techniques of the subject." 'iStatistics in Medical Research/i/ Updated and expanded to reflect the latest developments, iStatistical Methods for Survival Data Analysis, Fourth Edition/i continues to deliver a comprehensive introduction to the most commonly-used methods for analyzing survival data. Authored by a uniquely well-qualified author team, the Fourth Edition is a critically acclaimed guide to statistical methods with applications in clinical trials, epidemiology, areas of business, and the social sciences. The book features many real-world examples to illustrate applications within these various fields, although special consideration is given to the study of survival data in biomedical sciences./ Emphasizing the latest research and providing the most up-to-date information regarding software applications in the field, iStatistical Methods for Survival Data Analysis, Fourth Edition/i also includes:/ ulliMarginal and random effect models for analyzing correlated censored or uncensored data/liliMultiple types of two-sample and K-sample comparison analysis/liliUpdated treatment of parametric methods for regression model fitting with a new focus on accelerated failure time models/liliExpanded coverage of the Cox proportional hazards model/liliExercises at the end of each chapter to deepen knowledge of the presented material/li/ul iStatistical Methods for Survival Data Analysis/i is an ideal text for upper-undergraduate and graduate-level courses on survival data analysis. The book is also an excellent resource for biomedical investigators, statisticians, and epidemiologists, as well as researchers in every field in which the analysis of survival data plays a role.